2018
DOI: 10.1186/s12905-017-0465-0
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical hypothyroidism would not lead to female sexual dysfunction in Chinese women

Abstract: BackgroundThere is dearth of research about female sexual dysfunction (FSD), especially in China, because of conservative beliefs. Previous studies indicated the relationship between subclinical hypothyroidism and anxiety and depression. However, there is dearth of research regarding the relationship between subclinical hypothyroidism and FSD in Chinses women.MethodA hospital-based research was conducted. Female sexual function was measured by CVFSFI which includes 19 items. Participants were identified as FSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…In the initial database search, we have identified a total of 423 publications. After removing 416 records for various reasons, 7 studies 21 27 ultimately met our predefined inclusion criteria. A total of 2,703 individuals were involved, while the hypothyroidism cases were 460 (overt: 114; subclinical: 346).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the initial database search, we have identified a total of 423 publications. After removing 416 records for various reasons, 7 studies 21 27 ultimately met our predefined inclusion criteria. A total of 2,703 individuals were involved, while the hypothyroidism cases were 460 (overt: 114; subclinical: 346).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 2,703 individuals were involved, while the hypothyroidism cases were 460 (overt: 114; subclinical: 346). Among the 7 included studies, 5 studies 21 , 23 , 25 27 solely reported the cases of overt hypothyroidism or subclinical hypothyroidism, while 2 included studies 22 , 24 reported both overt hypothyroidism and subclinical hypothyroidism, resulting in 4 studies related to overt hypothyroidism and 5 studies related to subclinical hypothyroidism. There are 2 cross-sectional studies 21 , 25 and 5 case-control studies 22 24 , 26 , 27 published from 2006 to 2018 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies listed in Table 2 demonstrated a strong association between hypothyroidism and SD with a significant reduction of FSFI scores in hypothyroid women compared to controls (27,28,30,31,32). Different results are found in subclinical hypothyroidism: in fact, two studies performed on Asian women (33,34) contradict the association between sub-clinical hypothyroidism and SD found by Atis (28). However, the authors do not provide solid explanations for this inconsistency, only stating that subclinical hypothyroidism fails to achieve the elevated TSH levels commonly reported in overt hypothyroidism which can induce hyperprolactinemia.…”
Section: Hypothyroidismmentioning
confidence: 99%